Aortic endograft infection with Mycobacterium bovis following intravesical BCG immunotherapy diagnosed via the Karius Test™- case report and review of literature - Prateek Sharma; Kristin Schafer; Richard J. Hankins; Jonathan R. Thompson; Jason R. Cook (Annals of Vascular Surgery - Brief Reports and Innovations)
Bacillus Calmette-Guérin (BCG), a live attenuated form of Mycobacterium bovis, is utilized in non–muscle-invasive bladder cancer therapy. Disseminated BCG infection causing vascular graft infection is extremely rare. In this report, we review the literature and describe a rare case of aortic endograft infection in a 72- year-old man, who underwent intravesical BCG treatment four years ago that was diagnosed utilizing next generation sequencing technique via the Karius test™ enabling earlier diagnosis and treatment start compared to conventional microbiological diagnostic tools. The morbidity and mortality from aortic graft infections remain high, therefore prompt diagnosis and multidisciplinary approach is paramount.